Livedo reticularis and dengue - Pamo-Reyna, Oscar (2023)
We present the case of a 40-year-old male, resident of Lima city, with no recent travels, with fever, general malaise, headache and diarrhea. He went to the Emergency Department and auxiliary tests showed leukopenia and mild thrombocytopenia. Studies for Epstein-Barr, hepatitis B, toxoplasma, rubella, CMV, herpes 1-2 and COVID-19 were negative. IgM and IgG antibodies for dengue were negative and NS1 protein was positive. He was diagnosed with dengue. He only received paracetamol. On follow-up, on the seventh day of illness, he was found afebrile and with livedo reticularis type dermal lesions on the limbs, mainly. This unusual cutaneous pattern in dengue is highlighted.